TRENDS AND INSIGHTS OF GAMIFICATION IN LEARNING FOR SCIENCE EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Ajri, Alfiani Syarifatul; Wilujeng, Insih; Kuswanto, Heru (EduFisika: Jurnal Pendidikan Fisika, 2025)
Gamification is increasingly used in education. There are 20 articles on games in learning that highlight the importance of identifying game characteristics and their potential for science learning at the senior high school level. The data is sourced from publications indexed on Scopus from 2017 to 2024. Data collection used the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. The identification stage yielded 554 articles from Scopus. After screening, 50 articles met the criteria, and 20 final articles were analyzed in depth. The findings indicate that gamification has extensively incorporated both technology and traditional games. Trends in research reveal a significant focus on gamified products in chemistry, particularly for facilitating the comprehension of abstract concepts. Additionally, literature underscores the effectiveness of games as tools for enhancing learning and supporting material review. Research has shown that gamification in learning enhances various skills, such as learning outcomes, motivation, conceptual understanding, critical thinking, and mathematical representation. However, its influence on skills like collaboration, anxiety reduction, retention, cognitive abilities, academic performance, self-efficacy, and science literacy presents an area for further exploration. This study recommends that teachers apply digital gamification for abstract concepts and develop board games for collaborative contexts. Future research should expand gamification studies to physics and biology.